2017
DOI: 10.2141/jpsa.0160147
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Different Levels of Canola Meal on Performance, Organ Weights, Hepatic Deiodinase Gene Expression and Thyroid Morphology in Broiler Chickens

Abstract: This study was carried out to determine the effects of dietary inclusion level of canola meal (CM) on performance, organ weights and hepatic type I deiodinase gene expression in broilers. A completely randomized design with 4 levels of CM (0, 10, 20 and 30%) as a substitute for soybean meal (SBM) was utilized with 5 replicates of 9 birds each. The results showed that body weight gain (1 to 42 d) decreased linearly (P<0.01) as the inclusion of CM increased. An increase in dietary level of CM also resulted in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 47 publications
(92 reference statements)
1
3
3
Order By: Relevance
“…In this respect, Aljuobori et al (2016) suggested that glucosinolates in CM may destroy cellular T 3 receptors and thus increase the thyroid hormones level in blood. In contrary to our results, Taraz et al (2006); Mikulski et al (2012); Payvastegan et al (2017) indicated that an increasing of inclusion levels of CM was followed by plasma T 3 concentrations reduction. However, Taraz et al (2006); Payvastegan et al (2017) reported no significant differences in plasma T 4 among all experimental groups.…”
Section: Blood Biochemical Parameterscontrasting
confidence: 99%
See 2 more Smart Citations
“…In this respect, Aljuobori et al (2016) suggested that glucosinolates in CM may destroy cellular T 3 receptors and thus increase the thyroid hormones level in blood. In contrary to our results, Taraz et al (2006); Mikulski et al (2012); Payvastegan et al (2017) indicated that an increasing of inclusion levels of CM was followed by plasma T 3 concentrations reduction. However, Taraz et al (2006); Payvastegan et al (2017) reported no significant differences in plasma T 4 among all experimental groups.…”
Section: Blood Biochemical Parameterscontrasting
confidence: 99%
“…In contrary to our results, Taraz et al (2006); Mikulski et al (2012); Payvastegan et al (2017) indicated that an increasing of inclusion levels of CM was followed by plasma T 3 concentrations reduction. However, Taraz et al (2006); Payvastegan et al (2017) reported no significant differences in plasma T 4 among all experimental groups. They attributed these discrepancies to differences in glucosinolates content in CM, diet ingredients, composition of gut microorganism besides, the extent of glucosinolates degradation by heat during the oil extraction process (Woyengo et al, 2011).…”
Section: Blood Biochemical Parameterscontrasting
confidence: 99%
See 1 more Smart Citation
“…The function of the liver is to detoxify chemicals and metabolize drugs. It is known that the size of the liver increases in response to higher levels of chemical compounds requiring detoxification (Payvastegan et al, 2017 ). It was expected that higher levels of CM inclusion would induce higher liver activity leading to birds with bigger livers than those reared on the CM0 diet.…”
Section: Discussionmentioning
confidence: 99%
“…However, the presence of anti-nutritional factors ( ANF ) such as fibre (12%) and glucosinolates (3.8 µmol/g) (Disetlhe et al, 2018 ) in CM could hinder growth by interfering with nutrient digestion and absorption (Wickramasuriya et al, 2015 ) as well as carcass composition and meat quality in indigenous chickens. Indeed, these ANFs have been reported to reduce growth performance in broilers (Payvastegan et al, 2017 ) and quails (Moraes et al, 2015 ). Glucosinolates interfere with thyroid hormone synthesis, causing liver damage and appetite depression (Tripathi and Mishra, 2007 ).…”
Section: Introductionmentioning
confidence: 99%